Polychaete annelids as live bait in Portugal: Harvesting activity in brackish water systems. (1st November 2019) - Cabral, Sara; Alves, Ana Sofia; Castro, Nuno; Chainho, Paula; Sá, Erica; Cancela da Fonseca, Luís; Fidalgo e Costa, Pedro; Castro, João; Canning-Clode, João; Pombo, Ana; Costa, José Lino
Abstract: Polychaete annelids are some of the most heavily harvested invertebrates collected in coastal areas and estuaries for their economic value as live fishing bait or as food supplement in aquaculture activities. However, information on bait digging in Portugal is scarce or incomplete. Thus, the present study aimed at investigating the bait digging activity in the four most relevant brackish water systems in Portugal: Ria de Aveiro and Ria Formosa coastal lagoons and Tagus and Sado estuaries. Direct observations were performed in each brackish water system 1 h and a half before and after the diurnal low spring tide (<0.8 m height), on working days. Additionally, logbooks were delivered to bait diggers and two types of surveys were conducted in every system: one to all the intertidal users and the other only to bait diggers. The estimated daily weighted number of bait diggers varied between 31 in the Tagus estuary and 69 in the Ria Formosa coastal lagoon. Diopatra neapolitana (Delle Chiaje, 1841) was the main target species in Ria de Aveiro (more than 83%), Tagus estuary (more than 60%) and Ria Formosa (more than 90%), while in Sado estuary most of the bait diggers targeted Marphysa sp. (92.6%). The highest and lowest amount of polychaete annelid catches were estimated for Ria de Aveiro coastal lagoon (almost 50 tons per year) and Tagus estuary (11 tons per year), respectively. A total annual bait catch value in these four systems was estimated as €3.84 millions. The most important brackish water systems concerning bait diggers' number and bait captures were Sado estuary and Ria de Aveiro coastal lagoon where management measures should be considered, although managing polychaete harvesting activity is still difficult due to limited information on harvesting and on direct and indirect impacts on population dynamics. Highlights: Information regarding the harvest of polychaetes in Portugal is scarce. Surveys and bait diggers' observations were performed in four brackish water systems. Preferential areas and target species ( D. neapolitana & Marphysa sp.) were determined. A total annual bait catch value in the four systems was estimated as €3.84 millions. The establishment of rotational closed areas was proposed as a management measure.